Study on the Axial Compression Postbuckling Similitude Model of the Stiffened Cylindrical Shell with Dimple Imperfections. (20th April 2021) - Ding, Jiawei; Xing, Xinkui; Yu, Wei; Zhu, Wanxu
Abstract : The body of the new-type dry gas holder is a large stiffened cylindrical shell. Limited by the test site and economic conditions, the buckling characteristics of such holders are generally studied through scale model experiments. Taking the longitudinal-ring rectangular stiffened cylindrical shell as the research object, the generalized similitude condition and scaling principle formula of the structure are derived innovatively based on Donnell's assumption and the energy method. By means of displacement loading and node coordinates updating, dimple imperfections are introduced into the ideal structure of the stiffened cylindrical shell, and then, the complete similitude and partial similitude analysis of axial compression nonlinear buckling for imperfect structures are carried out. The analysis results show that the complete similitude analysis of stiffened cylindrical shell axial-compression nonlinear buckling can be realized accurately; the partial similitude model for stiffened cylindrical shell axial-compression nonlinear buckling can better predict the buckling characteristics of its prototype structures, and the closer the Poisson's ratio between the model and the prototype materials is, the more accurate the prediction results are. Meanwhile, the generalized similitude condition and scaling principle formula derived based on the energy method can provide useful reference for the model design and experimental verification of the axial compression buckling of the stiffened cylindrical shell with local geometric imperfections.